Pengaruh Persepsi, Pengetahuan, dan Kesadaran Wajib Pajak Terhadap Penghindaran Pajak - Sri Ayem; Maria Liliyanti Bete Mau (Yayasan Literasi Ilmiah Indonesia, 2025)
Purpose: This study aims to analyze the influence of taxpayer perception, taxpayer knowledge, and taxpayer awareness on tax avoidance among young entrepreneurs in Yogyakarta City. Additionally, the study also evaluates the simultaneous influence of these three variables on tax avoidance behavior, providing a deeper understanding of the factors influencing tax compliance among young entrepreneurs.The research design used in this study is a descriptive research design, which aims to describe the characteristics of the variables under study. The research population consists of young entrepreneurs in Yogyakarta City, while the sample consists of 100 young entrepreneurs. The data collection method used is a questionnaire, which was distributed to the respondents. The data were analyzed using descriptive statistics and regression analysis. The results of the study indicate Method: The research method used a quantitative approach with primary data collection through questionnaires distributed both directly and using the Google Forms online platform to 62 young entrepreneurs in the city of Yogyakarta. The research instrument was measured using a 4-point Likert scale and tested for validity and reliability using Cronbach's Alpha. Data analysis was performed using multiple linear regression with SPSS, and also tested classical assumptions including multicollinearity, heteroscedasticity, and data normality. Finding: The results of the study indicate that taxpayer perception, taxpayer knowledge, and taxpayer awareness partially and simultaneously have a positive and significant influence on the tax avoidance behavior of young entrepreneurs in Yogyakarta City. Tax awareness has the most dominant influence with the largest beta coefficient. Collectively, these variables can explain approximately 62.6% of tax avoidance behavior, indicating that the level of awareness, knowledge, and perception plays an important role in young entrepreneurs' decisions regarding tax obligations. Novelty: This study is novel in that it examines the influence of perception, knowledge, and awareness of taxpayers on tax avoidance specifically among MSME actors from among young entrepreneurs. Focusing on this group is important because they are a generation that is developing in the business world and has different tax behavior characteristics compared to conventional taxpayers. In addition, there is still little research highlighting the tax behavior of young MSME entrepreneurs, especially in the context of their awareness and understanding of tax obligations in the digital era.